Contribution of allosteric disulfide in the structural regulation of membrane-bound tissue factor–factor VIIa binary complex. Issue 14 (22nd September 2019) - Prasad, Ramesh; Banerjee, Suparna; Sen, Prosenjit
Abstract: Two distinct populations, active and cryptic forms of tissue factor (TF), reside on the cell surface. Apart from phospholipid contribution, various models have been introduced to explain decryption/encryption of TF. The proposed model, the switching of Cys186–Cys209 bond of TF, has become the matter of controversy. However, it is well accepted that this disulfide has an immense influence upon ligand factor VIIa (FVIIa) for its binding. However, molecular level understanding for this remains unveiled due to lack of detailed structural information. In this regard, we have performed the molecular dynamic study of membrane-bound TF/TF–FVIIa in both the forms (±Cys186–Cys209 allosteric disulfide bond), individually. Dynamic study depicts that disulfide bond provides structural rigidity of TF in both free and ligand-bound forms. This disulfide bond also governs the conformation of FVIIa structure as well as the binding affinity of FVIIa toward TF. Significant differences in lipid–protein interaction profiles of both the forms of TF in the complex were observed. Two forms of TF, oxidized and reduced, have different structural conformation and behave differentially toward its ligand FVIIa. This disulfide bond not only alters the conformation of GLA domain of FVIIa in the vicinity but allosterically regulates the conformation of the distantly located FVIIa protease domain. We suggest that the redox status of the disulfide bond also governs the lipid-mediated interactions with both TF and FVIIa. Communicated by Ramaswamy H. Sarma